The Sustainable Places 2017 (SP2017) Conference 2017
DOI: 10.3390/proceedings1070690
|View full text |Cite
|
Sign up to set email alerts
|

PVSITES: Building-Integrated Photovoltaic Technologies and Systems for Large-Scale Market Deployment

Abstract: Abstract:The large potential for energy savings in buildings led the EU Commission to adopt the 2010/31/EU Directive on the energy performance of buildings with the objective that all new buildings are Nearly Zero Energy Buildings (NZEB) by 2020. Renewable energy technologies, and in particular the integration of photovoltaic systems in the building environment offer many possibilities to play a key role within the NZEB scenario. The objective of PVSITES project is to drive BIPV technology to a large market de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…This was towards giving a definite and professionally reliable answer to the market requirements pre-identified by the industrial members of the consortium. It focuses on high impact demonstration and dissemination actions to be executed using cost-effective renewable generation, reduction of energy demands and smart energy management [75,77]. Plate 1.…”
Section: The Pvsites Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…This was towards giving a definite and professionally reliable answer to the market requirements pre-identified by the industrial members of the consortium. It focuses on high impact demonstration and dissemination actions to be executed using cost-effective renewable generation, reduction of energy demands and smart energy management [75,77]. Plate 1.…”
Section: The Pvsites Projectmentioning
confidence: 99%
“…Based on these requirements, we reviewed related studies on BIPV adoption, and we identified three (3) studies which focus on developed approaches to communicate BIPV. These include the International Energy Agency-IEA Task 41-SubTask C three-stage approach from client to design team to design-communication tools [74], the European-based use of "an ambitious demonstration project portfolio" [75], and an Architectural Integration Qualities (AIQ) model which initiates and focuses discussions on preferences for architectural integration of energy-producing solar shading [76]. The sub-sections which follow state an overview of these studies used to deduce core requirements for the proposed approach as a starting point for the design process.…”
mentioning
confidence: 99%
“…While such BAPV systems generate adequate electricity, their transparent area fraction is limited, which often makes them unattractive in architectural installations. A number of recent studies have been dedicated to uncovering the potential of renewable energy technologies including photovoltaics for reaching the important goal of net-zero energy consumption in buildings and infrastructural installations [13][14][15][16][17][18]. Figure 1 summarizes three well-known commercialized and recent examples of the relevant technologies and also provides the data on the currently-available electric power generation capacities per unit wall area.…”
Section: Introductionmentioning
confidence: 99%
“…During recent decades, multiple software suites have been developed to compute the solar irradiation impinging on a surface and the energy yield of a PV system. Among these, we can find: In My Backyard tool 7 , the PVSITES project 8 , different raytracing-based simulation tools [9][10][11] , various GIS-based methods 12,13 and many others 14 . The vast majority of these available tools calculate the hourly irradiance impinging on the plane of array (POA) considering the radiation intensity and distribution over the sky, the module tilt and orientation, and the objects surrounding the target surface 15 .…”
mentioning
confidence: 99%